2020
DOI: 10.1002/anie.202008806
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Specific C(sp3)–H Aminations of Imidates and Amidines Enabled by Covalently Tethered Distonic Radical Anions

Abstract: The utilization of N-centered radicals to synthesize nitrogen-containing compounds has attracted considerable attention recently,d ue to their powerfulr eactivities and the concomitant construction of CÀNb onds.H owever,t he generation and control of N-centered radicals remain particularly challenging.W er eport at ethering strategy using SOMO-HOMO-converted distonic radical anions for the site-specific aminations of imidates and amidines with aid of the noncovalent interaction. This reaction features aremarka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…Ultimately, the benzocyclic structure was found to be optimal for the intramolecular amination (56,7 6%, > 20:1 dr), and the cisdiastereoselectivity of 56 was also confirmed by the X-ray crystallographic analysis. [32] Furthermore,the late-stage functionalizations of the derivatives from the dehydrocholesterol and carbohydrate were performed successfully as well (57 and 58). Having successfully achieved the synthesis of the oxazoline and dihydro-1,3-oxazine derivatives (Figure 4a (Figure 5, bottom).…”
Section: Substrate Scopementioning
confidence: 97%
See 2 more Smart Citations
“…Ultimately, the benzocyclic structure was found to be optimal for the intramolecular amination (56,7 6%, > 20:1 dr), and the cisdiastereoselectivity of 56 was also confirmed by the X-ray crystallographic analysis. [32] Furthermore,the late-stage functionalizations of the derivatives from the dehydrocholesterol and carbohydrate were performed successfully as well (57 and 58). Having successfully achieved the synthesis of the oxazoline and dihydro-1,3-oxazine derivatives (Figure 4a (Figure 5, bottom).…”
Section: Substrate Scopementioning
confidence: 97%
“…In the further investigation, alcohols with the tertiary b CÀHb onds (23-25)a nd secondary alcohols (26, 27,b oth trans, > 20:1 dr;a nd 28, cis, > 20:1 dr) were b-aminated efficiently.T he trans-diastereoselectivity of b amino alcohol 26 was confirmed by the X-ray crystallographic analysis. [32] Notably,t he products with hydrolysis-sensitive substituents (29 and 30)were isolated as the oxazolines.Furthermore,the late-stage aminations of the small-molecule drug derivatives, carbohydrate analogue,a nd steroid-derived substrates were also successful in moderate to excellent yields (31-35,u pt o 99 %). [32] It was found that the introduction of the Natom to substrates bearing both 1,5-HATand benzylic 1,6-HATs ites realized the selectively b-aminations (39-41)d ue to that the generated radicals can be stabilized by the orbital overlap of al one pair on an adjacent heteroatom.…”
Section: Substrate Scopementioning
confidence: 99%
See 1 more Smart Citation
“…Complementing these molecular material applications, organic radicals with SHI have recently been claimed as key intermediates for regiospecific reaction of C(sp 3 )H-amination and photocatalytic allylation, providing alternative directions for organic synthesis. 80,81 Design strategies for SHI radicals Numerous molecular systems have been reported to show SHI. However, a clear understanding of the electronic factors that lead to this specific electronic configuration has been lacking.…”
Section: Somo-homo Inversion (Shi): Basic Considerationsmentioning
confidence: 99%
“…Intramolecular HAT mediated by nitrogen-centered radicals constitutes a valuable tool for the site-selective C­(sp 3 )–H functionalization of organic compounds. , In this context, much attention has been focused recently toward applying the iminyl-radical-mediated intramolecular 1,5-HAT to the preparation of benzene-fused cyclohexanones, nitrogen heterocycles, β-amino alcohols, and γ-functionalized ketones . Encouraged by these achievements, we set out to develop new C­(sp 3 )–H functionalization methods on the basis of this chemistry.…”
mentioning
confidence: 99%